TAXATION SYSTEM AND ANTI-TAX PROTESTS BY ANNANG WOMEN IN THE NIGERIAN COLONIAL STATE - Emmanuel Toby; Albert O. Onobhayedo (Romanian Journal of Historical Studies, 2022)
Women protest against obnoxious economic policies in Annang opened a new chapter in women’s quest for socio-political integration and economic empowerment and struggle against exploitation during the colonial period. Against the significant public roles women played in the pre-colonial times, British colonial authorities introduced exploitative economic policies and a native authority system that marginalised women. The burden women had to bear was compounded by the various taxes that were imposed on their husbands, which the British extended to them, subsequently. This paper focuses on the women’s opposition to direct and indirect taxation, ex-raying the causes, course and dramatis personae involved. The paper concludes that apart from the global economic depression, predatory leadership, crass opportunism and insincerity that prevailed, exploitative tax regimes and ineptitude on the part of tax administrators, were responsible for the anti-tax protests by women in Annang during the colonial period.